Pengembangan Materi Teks Negosiasi Berbasis Media Video Alight Motion - Elra Azmi Masfufah; Trisnawati Hutagalung (Universitas Suryakanca, 2022)
This article will describe the process of developing negotiation text material based on Alight Motion video media in class X IPS at SMA Negeri 7 Medan. The research was conducted using the Research & Development (R&D) approach with the method developed by Borg and Garl which was modified by Sugiyono. In the research, several stages were carried out, namely: a) potential and problems, b) data collection, c) product design, d) product validation, and e) product revision. The results showed that based on material expert validation, an average percentage of 88% was obtained and media experts obtained an average percentage of 90% and were included in the very good category. Therefore, overall it can be said that the feasibility of the product is in the very good category. The product of developing negotiation text material based on Alight Motion video media is in the form of a video with a duration of 10 minutes and 13 seconds which presents the main points of the material being taught as well as additional material for students related to negotiation texts such as understanding negotiation texts, negotiating text structures, linguistic rules of negotiation texts, how to identify persuasive sentences in the negotiating text, and write the negotiation text.Keywords: Alight Motion; media; negotiation textAbstrakArtikel ini akan mendeskripsikan proses pengembangan materi teks negosiasi berbasis media video Alight Motion di kelas X IPS SMA Negeri 7 Medan. Penelitian dilakukan menggunakan pendekatan Research & Development (R&D) dengan metode yang dikembangkan oleh Borg dan Garl yang dimodifikasi oleh Sugiyono. Dalam penelitian, dilakukan beberapa tahap, yakni: a) potensi dan masalah, b) pengumpulan data, c) desain produk, d) validasi produk, e) revisi produk. Hasil penelitian menunjukkan bahwa berdasarkan validasi ahli materi diperoleh rata-rata persentase 88% dan ahli media diperoleh rata-rata persentase 90% dan masuk dalam kategori sangat baik. Oleh karena itu, secara keseluruhan dapat dikatakan secara kelayakan produk berada dalam kategori sangat baik. Produk pengembangan materi teks negosiasi berbasis media video Alight Motion berupa video berdurasi 10 menit 13 detik yang menyajikan pokok-pokok materi yang tengah diajarkan serta sebagai materi tambahan siswa terkait teks negosiasi seperti: pengertian teks negosiasi, struktur teks negosiasi, kaidah kebahasaan teks negosiasi, cara mengindentifikasi kalimat persuasif dalam teks negosiasi, dan menuliskan teks negosiasi. Keywords: Alight Motion; media; teks negosiasi